ESTABLISHING THE SET OF TASKS AS A WAY TO IMPROVE EFFECTIVENESS OF ART AND DESIGN EDUCATION - Kucherovskaya, Veronika; Momotova, Liliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper presents a study in the field of art and design education and focuses on looking for ways to improve the effectiveness of education through establishing a set of consistent professional tasks and identifying the interdisciplinary relationship. The paper outlines patterns of the design education process. The objective of the study is to analyse the interlinkages between abstract tasks, life drawings and graphics design exercises that demonstrate individual creativity of students.